Barriers to cataract surgery in peri-urban regions of Eastern Nepal: An experience at a government eye department - Ansari, Zahir; Maharjan, Ravi Kumar; Basnet, Rakshya; Khatoon, Sahana; Koirala, Ashesh (Nepalese Journal of Ophthalmology, 2022)
NA